Doing SLA research with implications for the classroom reconciling methodological demands and pedagogical applicability - DeKeyser, Robert; Botana, Goretti Prieto (Language learning and language teaching, 2019)
"This book is unique in bringing together studies on instructed second language acquisition that focus on a common question: 'What renders this research particularly relevant to classroom applications, and what are the advantages, challenges, and potential pitfalls of the methodology adopted?' The empirical studies feature experimental, quasi-experimental and observational research in settings ranging from the classroom to the laboratory and CALL contexts. All contributors were asked to discuss issues of cost, ethics, participant availability, experimental control, teacher collaboration, and student motivation, as well as the generalizability of findings to different kinds of educational contexts, languages, and structures. This volume should be of interest to graduate students in second language research, practicing teachers who want some guidance to navigate the sometimes overwhelming array of publications, and to researchers who are planning studies on instructed second language learning or teaching and are looking to make principled decisions on which of the existing methodologies to adopt"--